Palliative care and oncology in Colombia : the potential of integrated care delivery (2021)
Palliative care is on the global health agenda, as only approximately 14% of people who require palliative care receive it [1]. TheWorld Health Organisation (WHO) defines palliative care as a care approach that “improves the quality of life of patients and that of their families who are facing challenges associated with life-threatening illness, whether physical, psychological, social or spiritual. The quality of life of caregivers improves as well”. To achieve universal health coverage, a core component of the United Nation’s sustainable development goal 3 (“Ensure healthy lives and promote well-being for all at all ages”), palliative care is a prerequisite [2,3]. Several randomised trials in cancer populations have demonstrated that early access to palliative care has significant benefits: for patients in terms of symptom burden, quality of life, end-of-life care [4–8]; for the healthcare system in terms of reduced financial burden for both patients and the health system [9]; and for informal family caregivers in terms of stress burden and depression [10]. A multinational consensus across Europe identified that palliative care should be delivered at both the “basic” and “specialised” levels, and called for recognition of palliative care in healthcare systems, including within oncology and primary care [11]. However, a recent survey of patients with advanced cancer identified unmet palliative care needs in nearly two thirds of patients [12], and some authors argue that palliative care is still in its infancy in most of the developing world [13].